Emergence of constant tilt angle for vector fields on flexible curves. Issue 1 (18th November 2019) - Brand, Christopher; Dolzmann, Georg
Abstract: A model for the evolution of vector fields on flexible curves is investigated. Explicit solutions with radial symmetry demonstrate global existence. Numerical simulations show that configurations with constant tilt angle emerge as stationary states.